Pengaruh Olahraga Teratur Terhadap Kadar Estrogen Adiposa dan Estrogen Serum pada Tikus Sprague dawley yang Dilakukan Ovariektomi - Eka Bebasari (Fakultas Kedokteran Universitas Riau, 2015)
Menopause has some effects on women’s health. Exercise is one alternative to resolve menopausal complaints.Regular exercise can increase serum estrogen level in postmenopausal women. This increase is believed to occurthrough increased aromatization of androgen in extragonadal tissue especially adipose tissue in postmenopausal women.The purpose of this study is to explore estrogen levels in adipose tissue and serum due to regular exercise inovariectomized rats. A post-test only control group design was performed in this study. Ten female Sprague dawleyrats were used throughout the study and randomly selected. Rats were ovariectomized and divided into two groups:five rats in treated group and five rats in control group. Treatment groups get treadmill exercise for 8 weeks. Furthermore,rats blood were taken for examination of serum estrogen level, rats were killed and subcutaneous abdominal adiposetissue were removed for examination of estrogen level in adipose tissue. Statistical analysis was performed withindependent t test. Estrogen level in adipose tissue was higher in the treatment group but not statistically significant (p> 0,05). Higher serum estrogen levels in the control group but not statistically significant (p > 0,05). Extragonadalaromatization has occurred in adipose tissue of ovariectomized rats with regular exercise.